Iatrogenic Enamel Lesions with Fixed Multi-bracket Treatment - Mukesh Kumar; Sommya Kumari; Sowmya Shree Guntipally; Ajay Chhabra; Ashok Kumar; Ratnesh Kumar; Ritesh Singh (Journal of Pharmacy and Bioallied Sciences)
Background: Malocclusion is a serious oral health issue that requires orthodontic correction. Fixed orthodontic appliances are known for acquired enamel damage. Aims: To evaluate the incidence of iatrogenic white spots in subjects treated with fixed orthodontic therapy. Methods and Materials: This was a retrospective study. The study sample included the orthodontically treated subjects debonded during the study period. An imaging technique was followed to evaluate enamel white spots. Teeth debonded after orthodontic therapy were evaluated and compared with pretreatment records. Results: A majority of subjects were young adults. Maximum subjects were school-going children from the rural background. Maxillary incisors were the most affected tooth, whereas maxillary posteriors were the least affected with white spot lesions. Conclusions: Iatrogenic enamel damage is the prime concern for orthodontists. Good oral hygiene maintenance and demineralization prevention is the ideal strategy.